A new species of Halisarca (Demospongiae: Halisarcida) from the Sea of Okhotsk, North Pacific - Ereskovsky, Alexander V. (Zootaxa, 2007)
A new species of sponge without skeleton, Halisarca korotkovae sp. nov. is described from the Sea of Okhotsk. It differs from the other species of Halisarca by its different ecological conditions, as well as by its morphology and histology. The new species is characterized by its fulvous colour and by its big nucleolated, eosinophilic microgranular cells (18.7×9.5 to 10.8×7.1 μm) concentrated mainly in the ectosomal part of sponge in aggregates up to 40 μm in diameter.